Fostering Creative Expression in Early Childhood Learners: Ekraf Academy and the Development of Visual Arts Skills in Baubau, Southeast Sulawesi - Machali, Imam; Shafa Masnaini Z, Bintang; Permata Bening, Tiara; Asri Fahma Rishanda, Waode (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Early childhood visual art learning is frequently reduced to routine, product-oriented activities, leaving limited scholarly attention to the micro-processes through which creativity is negotiated in practice. This instrumental case study examines how Ekraf Academy, a non-formal art program in Baubau, Southeast Sulawesi, Indonesia, structures conditions that support children’s creative visualization. Data were generated through an in-depth interview with the founder-instructor, participant observation across four naturally occurring sessions during a two-week field period in 2025, and analysis of children’s portfolios, artworks, and institutional documents. The dataset was analyzed using reflexive thematic analysis. The findings reveal that creative visualization develops through social-evaluative mediation, in which affective cues—such as peer attention and instructor reassurance—shape children’s formal decisions regarding color, line, and composition. The pedagogical design operates through structured flexibility characterized by several trade-offs: mentoring reduces fear of error while occasionally encouraging confirmation-seeking; an “Exploration Day” format expands artistic variety but increases initiation costs under conditions of high choice; and small-group proximity facilitates peer learning yet intensifies comparison pressures when participation levels differ. The study conceptualizes non-formal early childhood art learning as a context-sensitive ecology of creative decision-making, offering analytically transferable pedagogical principles for designing creativity-oriented art programs in early childhood education.